Bundling diabetes care delivery. Issue 5 (September 2015) - Lockhart, Lisa; Whaley, Deborah; Nay, Penelope
Abstract : In today's complex healthcare arena, it takes a multidisciplinary team to make it all work. Utilizing patient-centered, evidence-based bundled interventions is a win for quality disease management.